Sedimentology and Reservoir Potential of Lower Tanjung Sandstone in Martapura, Barito Basin, South Kalimantan - Widada, Sugeng; Prahastomi, Mochammad; Adha, Ikhwannur; Rizky, Aga (Universitas Proklamasi 45, 2024)
The Barito Basin in South Kalimantan, Indonesia, is a hydrocarbon-producing basin where the Eocene Tanjung Formation serves as both the primary source rock and reservoir. Despite historical discoveries, recent exploration has faced challenges in identifying high-quality reservoir rocks. This study evaluates the reservoir potential of the Lower Tanjung Formation in the Martapura area using fieldwork and laboratory analyses, focusing on porosity, permeability, and texture and depositional geometry. The formation comprises thick shale with minor sandstone and coal layers, interpreted to be deposited in an estuarine environment. Sandstone layers, 0.2–12 m thick, are limited in lateral extent, forming a narrow